Toxicity of treatment regimens for drugresistant tuberculosis. - G. N. Mozhokina; Yu. R. Zyuzya; L. Yu. Petrova; A. G. Samoilova; I. A. Vasilyeva (Антибиотики и Химиотерапия, 2022)
Background. The main factors reducing treatment effectiveness in patients with pulmonary tuberculosis are as follows: the growing drug resistance of mycobacteria, which necessitates the strengthening of chemotherapy regimens, the use of new antimicrobial drugs, as well as poor tolerability of treatment due to the high frequency of adverse drug reactions. Combinations of fluoroquinolones, bedaquiline, and linezolid with traditional anti-tuberculosis drugs are used in new regimens for the treatment of patients with multidrug- and extensively drug-resistant tuberculosis, but the safety of new regimens has yet to be sufficiently studied.The aim was to study the features of toxic effect manifestations of the 5-component antimycobacterial drug complexes in an experiment on rats.Methods. The study was carried out on 64 non-pedigree rats, old females, divided equally into 3 experimental groups and 1 control. Rats of the experimental groups received drug complexes at doses corresponding to therapeutic doses for humans. The complexes’ base components were: moxifloxacin, bedaquiline, linezolid, and capreomycin. The fifth drug in group 1 was prothionamide, in the 2nd — pyrazinamide, in the 3rd — cycloserine. After 14 and 28 days of administration, the clinical picture of intoxication, ECG results, behavioral reactions of rats in the open field test, biochemical blood and urine tests, as well as pathomorphological studies were analysed.Results. Progressive damage to the gastrointestinal tract, liver, kidneys, and central nervous system was observed in rats of all experimental groups. The leading reason of polytoxicity is the nephrotoxic effect caused by capreomycin, to which rats have a high species sensitivity. In group 1, rats were treated with three drugs possessing potential cardiotoxicity; cardiotoxic effect was observed in the form of prolongation of the QT interval on the ECG after 14 days of administration. The most toxic combination of drugs was the one used in rats of the 3rd group, it was enhanced by the addition of neurotoxic cycloserine, which led to the death of more than a third of the animals by the end of the experiment.Conclusion: the use of multicomponent combinations of antimycobacterial drugs, similar in safety profile, increases the risk of developing combined toxic reactions.